The Supreme Court and the development of law : through the prism of prisoners' rights - Smith, Christopher E. (Palgrave Macmillan, 2016)
This text illuminates the decision-making processes of the US Supreme court through an examination of several prisoners' rights cases. In 1964, the Supreme Court declined to hear prisoners' claims about religious freedom. In 2014, the Supreme Court heard a case that led to the justices' unanimous endorsement of a Muslim prisoner's religious right to grow a beard despite objections from prison officials. In the 50-year span between those two events, the Supreme Court developed the law concerning rights for imprisoned offenders. As demonstrated in this book, the factors that shape Supreme Court decision making are well-illustrated by prisoners' rights cases.